Neuropsychiatric Profile as a Predictor of Cognitive Decline in Mild Cognitive Impairment - Roberto, Natalia; Portella, Maria J.; Marquié, Marta; Alegret, Montserrat; Hernández, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Abdelnour, Carla; Esteban de Antonio, Ester; Tartari, Juan P.; Vargas, Liliana; López-Cuevas, Rogelio; et al. (Frontiers in Aging Neuroscience, 2021)
Mild cognitive impairment is often associated with affective and other neuropsychiatric symptoms (NPS). This co-occurrence might have a relevant impact on disease progression, from MCI to dementia. The aim of this study was to explore the trajectories of cognitive decline in an MCI sample from a memory clinic, taking into consideration a perspective of isolated cognitive functions and based on NPS clusters, accounting for the different comorbid symptoms collected at their baseline visit. A total of 2137 MCI patients were monitored over a 2.4-year period. Four clusters of NPS (i.e., Irritability, Apathy, Anxiety/Depression and Asymptomatic) were used to run linear mixed models to explore the interaction of cluster with time on cognitive trajectories using a comprehensive neuropsychological battery (NBACE) administered at baseline and at the three subsequent follow-ups. A significant interaction between cluster and time in cognitive decline was found when verbal learning and recognition were explored (p=0.002 for both memory functions). For verbal recognition, the Irritability cluster had the largest effect size (0.69), whereas the Asymptomatic cluster showed the smallest effect size (0.22). For verbal recognition, the Irritability cluster had the largest effect size among groups (0.64), and Anxiety/Depression had the smallest effect size (0.21). In MCI patients, the Irritability and Apathy NPS clusters shared similar patterns of worsening in memory functioning, which could point to these NPS as risk factors of a faster cognitive decline, acting as early prognostic markers and helping in the diagnostic process.